Review of Current Situation and Tendencies in Development of of Power System of Vietnam - Tuan Kiet Ngo; Thu Nga Nguen (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper gives an analysis of power system in Vietnam. Data on power resources of the country and forecasts pertaining to production and consumption (oil, gas and solid fuel) up to 2020 are cited in the paper.